Polyimide dielectric film and preparation method and application thereof
By modifying the aromatic structure of polyimide dielectrics, it suppresses electron movement and forms an internal electric field, it solves the problem of degradation of energy storage characteristics of polymer dielectrics under extreme high temperature conditions, and achieves efficient charging and discharge and high glass transitions temperature.
Patent Information
- Application Number
- CN202411602730.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-11
AI Technical Summary
It is difficult for existing polymer dielectrics to achieve high energy storage density, high charge and discharge efficiency and high glass transition temperature at the same time under extremely high temperature conditions, and leakage current is prone to decrease in energy storage characteristics.
By fluorine modification of the aromatic structure of polyimide (PI), an internal electric field is formed to induce electron migration and hinder electron movement, thereby inhibiting the formation of leakage current while maintaining high heat resistance of PI.
Under extremely high temperature conditions of 200℃, the polyimide dielectric film has lower leakage current loss, higher glass transition temperature and higher charge and discharge efficiency, with a charge and discharge efficiency of nearly 90%, and discharge energy. The density is significantly improved.
Smart Images

Figure CN119431845A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of materials, and in particular to a polyimide dielectric film and a preparation method and application thereof. Background Art
[0002] Today, the power grid is continuously promoting the construction of new power systems and developing in the direction of digitalization and intelligence, which puts forward higher requirements for energy storage applications. Film capacitors are an important energy storage component. In order to obtain larger capacity and better performance, it is urgent to improve the energy storage density and charging and discharging efficiency of capacitors. At present, film capacitors usually use polymer-type dielectrics. However, these ordinary polymer dielectrics are prone to excessive leakage current when operating in an environment above 100°C, resulting in a decrease in energy storage characteristics, and it is difficult to work for a long time under extremely high temperature conditions.
[0003] The current mainstream solutions include improving molecular structure, blending modification, covalent cross-linking, etc. Molecular structure design is to add strongly polar dipole groups to the main chain or side chain of linear polymers to increase the glass transition temperature. However, if the main chain contains a large amount of this structure, the leakage current of the material will increase significantly at high temperatures, resulting in a decrease in charge and discharge efficiency. The blending strategy is to mix polymer dielectrics with molecular semiconductors or another polymer in a certain proportion into a nanocomposite material to increase the dielectric constant of the original dielectric. However, the chemical bonds and dielectric properties of the two materials generally mixed are often different, and it is difficult to have good compatibility, resulting in local electric field distortion at the interface between the filler and the polymer, and the breakdown strength and maximum discharge energy density of the material decrease. The cross-linking method is to fix the polymer chain through a network formed by covalent bonds to improve the breakdown strength and discharge efficiency of the dielectric. Since the cross-linking conditions of polymer dielectrics and the manufacturing conditions of thin film capacitors are often different, and the change in cross-linking degree is not easy to control, the cost is that it will have an adverse effect on the energy storage characteristics of the capacitor at high temperatures. It can be seen that these methods are difficult to take into account multiple material properties such as high energy storage density, high charge and discharge efficiency and high glass transition temperature at the same time, and often sacrifice other properties in order to improve one property. Therefore, it is hoped that a polymer dielectric material with high dielectric constant and low dielectric loss can be found under extremely high temperature conditions.
[0004] Polyimide (PI) is a polymer with excellent mechanical properties and stable chemical properties. The effect of the benzene ring and the imide ring in the molecule makes it have a very high glass transition temperature, so it is considered to be a dielectric material with great potential. However, the unique aromatic structure of PI makes it very difficult to achieve the characteristics of high temperature resistance and high energy density at the same time: on the one hand, PI can continue to work under high temperature conditions above 200°C. This is because its unique aromatic structure gives the material much stronger thermal stability than other polymers; on the other hand, the discharge energy density of PI at 200°C is about 0.26J / cm-3, and the energy loss reaches nearly 60%. The reason is that the aromatic structure of traditional PI will produce a large leakage current when electron displacement is aggravated under high temperature and strong electric field, thereby reducing its discharge energy density.
[0005] Therefore, in order to obtain PI with better energy storage properties, its structure needs to be improved. Summary of the invention
[0006] In view of the above defects, the present invention innovatively fluorine-modifies the aromatic structure in PI, forms an internal electric field in the PI molecular chain to induce electron migration, affects the electron distribution and hinders its movement, so as to suppress the formation of leakage current. While ensuring the high heat resistance of PI, it alleviates the problem of excessive leakage current and improves the discharge density and charge-discharge efficiency at the same time.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A method for preparing a polyimide dielectric film, the method comprising the following steps:
[0009] (1) 9,9-bis(4-(4-aminophenoxy)phenyl)fluorene PDA and 1,4-dioxane are dissolved in a solvent, and then cesium fluoride is added, followed by stirring for 20 to 35 minutes in an oxygen-free environment, and finally reacting for 18 to 20 hours at a temperature of 75 to 85° C. and stirring. The reaction mixture is filtered to obtain fluorine-modified 4,4′-(((9H-fluorene-9,9-diyl)bis(4,1-phenylene))di(oxy))diphenylamine FPDA;
[0010] (2) FPDA is dissolved in a solvent, and then diphenyl ether dianhydride is added in batches at -5 to 5°C and stirred for 8 to 10 hours to obtain a polyamic acid PAA solution. The solution is dropped onto a glass substrate and subjected to a thermal imidization reaction. After the reaction is completed, the glass substrate is placed in deionized water to peel off the film, thereby obtaining a PI-FP film with a thickness of 1 to 20 μm.
[0011] In the technical solution of the present invention: in step (1), the mass ratio of 9,9-bis(4-(4-aminophenoxy)phenyl)fluorene PDA, 1,4-dioxane and cesium fluoride is 3-4:35-47:1.5-2.5.
[0012] In the technical solution of the present invention: the solvent used in step (1) and step (2) is methyl pyrrolidone.
[0013] In the technical scheme of the present invention: the conditions for the thermal imidization reaction treatment in step (2) are 55-65° C. for 0.5-1.5 h, 110-130° C. for 1-3 h, 190-210° C. for 1-3 h, 240-260° C. for 0.5-1.5 h, and 300-320° C. for 0.5-1.5 h.
[0014] In the technical solution of the present invention: in step (2), the FPDA doping mass fraction in the thin film PI-FP is 1 to 10%wt.
[0015] A polyimide dielectric film is prepared by the above method.
[0016] In the technical solution of the present invention, the film prepared by the above method is used as a capacitor material.
[0017] Beneficial effects of the present invention:
[0018] (1) The present invention prepares fluorine-modified polyimide (PI-FP), which can inhibit the flow of electrons. While maintaining the high heat resistance of the original PI, it has lower leakage current loss, higher glass transition temperature and charge and discharge efficiency, and has comprehensive excellent energy storage characteristics.
[0019] (2) Starting from the overall molecular structure, the present invention proposes a fluorine-modified electron-induced shift strategy based on the aromatic structure of PI. First, the introduction of fluorine-modified fluorenediamine can improve the spatial structure of PI and increase the molecular chain spacing, thereby improving the glass transition temperature and polarization ability of the material; secondly, fluorine-modified fluorenediamine can regulate the energy band structure of PI polymer molecules, and the energy gap difference of polymer molecular orbitals becomes larger, so the energy required for electronic excitation increases, and the movement of electrons is inhibited, thereby reducing the leakage current density; the molecular orbital energy gap difference and the obstruction of electronic excitation greatly reduce energy loss, ultimately resulting in a charge and discharge efficiency of the PI-FP material of nearly 90%.
[0020] (3) The polymer dielectric film capacitor material prepared by the present invention can also work stably under extremely high temperature conditions of 200°C, and has comprehensive excellent energy storage performance: the glass transition temperature rises to 264.07°C; under an electric field strength of 200MV / m, the leakage current density increases from 7.1×10 -7 A / cm2 Down to 2.8×10 -8 A / cm 2 , and the charge and discharge efficiency reached 82.32%, an increase of 927.83% compared with PI; the discharge energy density increased to 5.324J / cm 3 . BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Infrared spectroscopic characterization of PDA and FPDA.
[0022] Figure 2 Comparison of maximum discharge energy density and volume resistivity of PI and PI-FP.
[0023] Figure 3 DE loop test results of PI at 200°C.
[0024] Figure 4 DE loop test results of PI-FP at 200°C.
[0025] Figure 5 The discharge energy density and charge-discharge efficiency of PI and PI-FP at 200°C. DETAILED DESCRIPTION
[0026] The present invention is further described below in conjunction with embodiments, but the protection scope of the present invention is not limited thereto:
[0027] Example 1
[0028] At room temperature, 3.218 g of 9,9-bis(4-(4-aminophenoxy)phenyl)fluorene (PDA) and 42.0 mL of 1,4-dioxane were dissolved in a methylpyrrolidone solution, 1.914 g of cesium fluoride (CsF) was added, and stirred for 30 min under a N2 atmosphere, then heated to 80 °C and stirred for 20 h. After cooling to room temperature, the reaction mixture was filtered to obtain fluorine-modified 4,4'-(((9H-fluorene-9,9-diyl)bis(4,1-phenylene))di(oxy))diphenylamine (FPDA).
[0029] Preparation process of PI-FP filmFPDA was dissolved in methyl pyrrolidone (NMP) solution and stirred for 2 hours. At 0°C, diphenyl ether dianhydride was added in 8 portions and stirred for 10 hours to obtain a uniform polyamic acid (PAA) solution. The solution was dropped onto a clean glass substrate and subjected to a thermal imidization reaction with a temperature gradient of 60°C / 1h, 120°C / 1h, 200°C / 2h, 250°C / 1h, and 300°C / 1h. After cooling to room temperature, the glass substrate was placed in deionized water to peel off the film, and a polymer film PI-FP containing 5wt% of FPDA doping mass fraction was obtained with a thickness of about 10μm.
[0030] Example 2
[0031] Other conditions were the same as those in Example 1, except that the FPDA doping mass fraction in the polymer film PI-FP was 1% wt.
[0032] Example 3
[0033] Other conditions were the same as those in Example 1, except that the FPDA doping mass fraction in the polymer film PI-FP was 3% wt.
[0034] Example 4
[0035] Other conditions were the same as those in Example 1, except that the FPDA doping mass fraction in the polymer film PI-FP was 7% wt.
[0036] Example 5
[0037] Other conditions were the same as those in Example 1, except that the FPDA doping mass fraction in the polymer film PI-FP was 9% wt.
[0038] Comparative Example 1
[0039] PI film preparation process :4,4'-diaminodiphenyl ether was dissolved in methyl pyrrolidone (NMP) solution and stirred for 2h. At 0℃, diphenyl ether dianhydride was added in six portions and stirred for 8h to obtain a uniform polyamic acid (PAA) solution, wherein the molar ratio of 4,4'-diaminodiphenyl ether to diphenyl ether dianhydride was 1:20. The solution was dropped onto a clean glass substrate and subjected to thermal imidization treatment, with a temperature gradient of 60℃ for 1h, 120℃ for 2h, 200℃ for 2h, 250℃ for 1h, and 310℃ for 1h. After cooling to room temperature, the glass substrate was placed in deionized water to peel off the film, and a film without FPDA and about 10μm in thickness was obtained.
[0040] Determination of breakdown strength:
[0041] The sample was immersed in silicone oil and the breakdown strength was tested using a digital temperature control board. The voltage was gradually increased at a gradient of 2000 V / s using a voltage transformer.
[0042] Table 1
[0043] Film breakdown field strength / (MV / m) Example 1 724.4 Example 2 607.3 Example 3 649.2 Example 4 687.8 Example 5 662.1 Comparative Example 1 317.8
[0044] It can be seen from the above table that adjusting the FPDA doping mass fraction in the PI-FP composite film has a significant effect on its breakdown field strength. This is because within a certain range, the breakdown field strength of the film is proportional to the FPDA doping mass fraction. Beyond this range, the breakdown field strength of the film begins to decrease.
[0045] Other performance tests (based on Comparative Example 1 and Example 1 below)
[0046] Infrared spectroscopy characterization:
[0047] The wavenumbers in the range of 500 to 3500 cm were recorded using a Nicolet iS50 spectrometer. -1 Fourier transform infrared spectroscopy in the range of . The polymer film was tested by X-ray diffraction (XRD) using a Panalytical BV diffractometer, and the amorphous peak in the range of 5-70° was determined. Figure 1 As shown, 1331cm -1 The stretching vibration peak at 3200-3500 cm -1 The stretching vibration peaks between 3200 and 3500 cm-1 in FPDA contain both -OH and -NH2 groups. -1 The stretching vibration peaks between the two groups become sharper, indicating that the large and broad stretching vibration peak of -OH disappears due to fluorine substitution, leaving only the stretching vibration peak of -NH2. This confirms the success of fluorine substitution.
[0048] The dielectric properties test results of the present invention are as follows:
[0049] The DSC3+ calorimeter was used to measure the dielectric constant and dielectric loss of the samples in a nitrogen atmosphere at 25-300°C according to differential scanning calorimetry (DSC). The test frequency range was 100-10 6 Hz, voltage is 0.5kV, temperature is 200℃. Figure 2 As shown in the figure, the volume resistivity of PI-FP is 1.21×10 14 Ω·cm 2 Increased to 9.23×10 14 Ω·cm 2 , which is 673.95% higher than the original one. At 200℃, the maximum discharge energy density of PI-FP is 0.371J / cm 2Increased to 5.324J / cm 2 , an increase of 1335.04% over the original.
[0050] The charging and discharging energy storage characteristics of film capacitors are as follows:
[0051] The PK-FERRO20B ferroelectric tester was used to measure the unipolar displacement-electric field (DE) loop at a test frequency of 100 Hz. The film samples were immersed in silicone oil and the breakdown strength was tested by controlling the temperature using a digital hot plate equipped with a thermocouple. A voltage transformer was used to apply voltage at a ramp rate of 200 V / s. The energy storage performance of PI and PI-FP at high temperatures was evaluated using the DE loop method. Figure 3 and Figure 4 As shown in the figure, the breakdown voltage of the film increased from 322.9MV / m to 684.4MV / m, a maximum increase of 124%. PI derivatives coated with fluorinated diamines exhibited narrower DE loops and lower residual polarization. Among them, the energy storage performance of PI-FP at high temperature was significantly enhanced, exceeding that of PI, and had a smaller residual polarization. Figure 5 As shown in Figure 2, the energy loss of the PI dielectric film increases sharply when the breakdown field strength is only 350 MV / m, reaching 1.09 J / cm 3 The energy loss of PI-FP film is even smaller, only 0.57 J / cm at an electric field strength of 600 MV / m. 3 This is because the molecular orbital spacing becomes larger after coating with FPDA and the charge excitation and transfer process is suppressed, resulting in an efficiency of nearly 90%.
Claims
1. A method for preparing a polyimide dielectric film, characterized in that: The method comprises the following steps: (1) 9,9-bis(4-(4-aminophenoxy)phenyl)fluorene PDA and 1,4-dioxane are dissolved in a solvent, and then cesium fluoride is added, followed by stirring for 20 to 35 minutes in an oxygen-free environment, and finally reacting for 18 to 20 hours at a temperature of 75 to 85° C. and stirring. The reaction mixture is filtered to obtain fluorine-modified 4,4′-(((9H-fluorene-9,9-diyl)bis(4,1-phenylene))di(oxy))diphenylamine FPDA; (2) FPDA is dissolved in a solvent, and then diphenyl ether dianhydride is added in batches at -5 to 5°C and stirred for 8 to 10 hours to obtain a polyamic acid PAA solution. The solution is dropped onto a glass substrate and subjected to a thermal imidization reaction. After the reaction is completed, the glass substrate is placed in deionized water to peel off the film, thereby obtaining a PI-FP film with a thickness of 1 to 20 μm.
2. The method for preparing a polyimide dielectric film according to claim 1, characterized in that: In step (1), the mass ratio of 9,9-bis(4-(4-aminophenoxy)phenyl)fluorene PDA, 1,4-dioxane and cesium fluoride is 3-4:35-47:1.5-2.
5.
3. The method for preparing a polyimide dielectric film according to claim 1, characterized in that: The solvent used in step (1) and step (2) is methyl pyrrolidone.
4. The method for preparing a polyimide dielectric film according to claim 1, characterized in that: The conditions for the thermal imidization treatment in step (2) are 55-65° C. for 0.5-1.5 h, 110-130° C. for 1-3 h, 190-210° C. for 1-3 h, 240-260° C. for 0.5-1.5 h, and 300-320° C. for 0.5-1.5 h.
5. The method for preparing a polyimide dielectric film according to claim 1, characterized in that: In step (2), the FPDA doping mass fraction in the thin film PI-FP is 1 to 10% wt.
6. A polyimide dielectric film, characterized in that: The film is prepared by any one of the methods of claims 1 to 5.
7. Use of the film prepared by the method of claim 1 as a capacitor material.
Citation Information
Patent Citations
Diamine monomer containing diphenylamine-fluorene, preparation method and application of same in polyimide preparation
CN105085281A
Polyimide dielectric film and preparation method and application thereof
CN111234529A
High-polarization and low-dielectric fluorinated polyimide film and preparation method thereof
CN117903470A
Polyimide film, flexible printed board, substrate for LED lighting and front plate for flexible display
WO2017057247A1
Cited By
High-adhesion and high-transparency liquid crystal polyimide film and preparation method thereof
CN121718048A